Bringing integration home: Policy on health and social care integration in the four nations of the UK. Issue 2 (18th April 2017) - Kaehne, Axel; Birrell, Derek; Miller, Robin; Petch, Alison
Abstract : Purpose: The purpose of this paper is to outline relevant policies on the integration of health and social care (HSC) in the four home nations: Scotland, Wales, Northern Ireland and England and offer a comparison of emphasis and approaches and draw out general insights on the implementation of integrated care policy. Design/methodology/approach: The paper is written as a piece of critical reflection by drawing on the authors' knowledge and expertise and wider evidence where available. Findings: Since 2010, HSC integration has started to diverge significantly in the four constituent countries of the UK. Although England and Wales have undergone considerable re-organisation of the NHS, Scotland and Northern Ireland have largely been marked by organisational continuity. However, beyond organisational differences, policy approaches, policy emphases and implementation strategies have also started to show considerable dissimilarity across the UK. An important contributory factor may be different ideological perspectives on the role of competition and pilots, partnership, patient choice and organisational incentives to bring about change in the field. Research limitations/implications: The paper identifies a serious lack of comparative research in integration policy, despite the considerable opportunities for quasi-experimental studies. This lack of empirical research impedes shared learning across the home nations. Originality/value: The paper presents a descriptive comparison of current integration policy between HSC providers in the four home nations. It reveals considerable opportunities for further research and comparative modelling of integration approaches.